Knowledge management in the Malaysian Armed Forces: a study on perceptions and applications in the context of an information and communication technology environment / Ismail Manuri - Manuri, Ismail (Institute of Graduate Studies, UiTM, 2012)
The development of modern warfare is reflected by the rising importance of having knowledge advantage over adversaries. Leadership, sense making, problem solving and decision-making are more complex and more demanding in military situations. Command and control is taking on new dimensions, and the role of military personnel is evolving into that of ‘thinking soldier’. The “information superiority” becomes the determinant of the future war management and requires a drastic improvement in information management, assurance, exchanging and sharing of superior knowledge. The aim of the study is to examine the attitude of the MAF officers’ towards Knowledge Management that include knowledge creation, Knowledge Management processes, Knowledge Management applications, and technology.